Research morphological and anatomical structure of herb Cyperus esculentus (Cyperus esculentus L.) - I. M. Ivasiuk; S. M. Marchyshyn; L. I. Budniak (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2019)
Cyperus esculentus (edible galingale, chufa, earth almond, tiger nutsedge) – Cyperus esculentus L. of the sedge family (Cyperaceae) today belongs to the new plant food resources used by mankind. This species can compete with traditional oilseed. In Ukraine, the Chufa culture has been known since the beginning of the XX century. The aim of the work is to study of the morphological and anatomical structure of the herb of the cyperus esculentus, suggested by the Department of New Cultures of the National Botanical Garden of the National Academy of Medical Sciences of Ukraine named after M. M. Hryshko, and establishing its main diagnostic features.